Electra to the rescue : saving a steamboat and the story of Shelburne Museum - Biebuyck, Valerie (David R. Godine, 2008)
Takes a look at the Shelburne Museum in Vermont, devoted to American folk art, and Electra Havemeyer Webb who founded it.